Investigating dam reservoir operation optimization using metaheuristic algorithms - Lai V.; Essam Y.; Huang Y.F.; Ahmed A.N.; El-Shafie A. (Springer Science and Business Media Deutschland GmbH, 2023)
Dams; Digital storage; Heuristic algorithms; Optimal systems; Reservoir management; Reservoirs (water); Time series analysis; Dam reservoir operation optimization; Dam reservoirs; Harris hawk optimization; Levy flights; Levy-flight whale optimization algorithm; Metaheuristic; Optimisations; Optimization algorithms; Reservoir operation optimizations; Whale optimization algorithm; Optimization; algorithm; dam; hydroelectric power; optimization; power generation; reservoir; water storage; Iran